Clinical Features, Treatment, and Surveillance of Hyperparathyroidism-Jaw Tumor Syndrome: An Up-to-Date and Review of the Literature - Francesca Torresan; Maurizio Iacobone (International Journal of Endocrinology)
Hyperparathyroidism-jaw tumor (HPT-JT) syndrome is an autosomal dominant disorder characterized by parathyroid tumors in association with fibro-osseous jaw tumors and uterine and renal lesions. HPT-JT syndrome is caused by germline mutations of the cell division cycle 73 (CDC73) gene that encodes the parafibromin, a 531-amino acid protein with antiproliferative activity. Primary hyperparathyroidism is the main finding of HPT-JT syndrome, usually caused by a single-gland parathyroid involvement (80% of cases), at variance with other variants of hereditary hyperparathyroidism, in which a multiglandular involvement is more frequent. Moreover, parathyroid carcinoma may occur in approximately 20% of cases. Surgery is the treatment of choice for primary hyperparathyroidism, but the extent of surgery remains controversial, varying between bilateral neck and focused exploration, with subtotal or limited parathyroidectomy. Recently, more limited approaches and parathyroid excisions have been suggested in order to decrease the risk of permanent hypoparathyroidism, the main surgical morbidity following more extensive surgical approaches. Ossifying fibromas of the mandible or maxilla may present only in a minority of cases and, even if benign, they should be surgically treated to avoid tumor growth and subsequent functional limitations. Benign and malignant uterine involvement (including leiomyomas, endometrial hyperplasia, adenomyosis, multiple adenomyomatous polyps, and adenosarcomas) is the second most common clinical feature of the syndrome, affecting more than 50% of CDC73-carrier women. Genetic testing should be performed in all family members of affected individuals, in young patients undergoing surgery for primary hyperparathyroidism, or in presence of other associated tumors, allowing early diagnosis and prompt treatment with more tailored surgery. Moreover, CDC73 mutation carriers should be also periodically screened for primary hyperparathyroidism and the other associated tumors. The present review was aimed to summarize the main clinical features of HPT-JT syndrome, focusing on genetic screening and surgical treatment, and to revise the available literature.